2021
DOI: 10.1371/journal.pone.0254155
|View full text |Cite
|
Sign up to set email alerts
|

Roles of parasympathetic outflow and sympathetic outflow in the cardiovascular response to brief umbilical cord occlusion in fetal sheep

Abstract: Fetal heart rate (FHR) deceleration is the most common change seen during labor. The role of the autonomic nervous system in regulating the fetal cardiovascular response during multiple uterine contractions has been well-established. However, the mechanism underlying the hemodynamic response remains unclear and the specific reflex that mediates the cardiovascular modifications is still controversial. This study aimed to determine the role of the sympathetic and parasympathetic systems on fetal hemodynamics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…During the first and second quarters, FHR during the reperfusion period was considerably higher in the vagotomy group than in the control group, probably reflecting the unopposed effects of high circulating catecholamines in the absence of parasympathetic tone (Galinsky et al., 2014, 2016; Lear, Beacom, Kasai, et al., 2020; Recher et al., 2021). In turn, this indicates that there is high parasympathetic activity between UCOs that markedly restrains FHR in control fetuses (Lear, Beacom, Westgate, et al., 2020; Lear, Westgate, Kasai, et al., 2020; Recher et al., 2021; Tournier et al., 2022). This tachycardia in the vagotomy group progressively reduced in magnitude, with less difference compared with the control group in the third and fourth quarters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During the first and second quarters, FHR during the reperfusion period was considerably higher in the vagotomy group than in the control group, probably reflecting the unopposed effects of high circulating catecholamines in the absence of parasympathetic tone (Galinsky et al., 2014, 2016; Lear, Beacom, Kasai, et al., 2020; Recher et al., 2021). In turn, this indicates that there is high parasympathetic activity between UCOs that markedly restrains FHR in control fetuses (Lear, Beacom, Westgate, et al., 2020; Lear, Westgate, Kasai, et al., 2020; Recher et al., 2021; Tournier et al., 2022). This tachycardia in the vagotomy group progressively reduced in magnitude, with less difference compared with the control group in the third and fourth quarters.…”
Section: Discussionmentioning
confidence: 98%
“…During the first and second quarters, FHR during the reperfusion period was considerably higher in the vagotomy group than in the control group, probably reflecting the unopposed effects of high circulating catecholamines in the absence of parasympathetic tone (Galinsky et al, 2014(Galinsky et al, , 2016Recher et al, 2021). In turn, this indicates that there is high parasympathetic activity between UCOs that markedly restrains FHR in control fetuses Recher et al, 2021;Tournier et al, 2022). This tachycardia in the vagotomy group progressively reduced in magnitude, with less difference compared with the control group in the third and fourth quarters.…”
Section: Control Of Fetal Heart Rate During and Between Decelerationsmentioning
confidence: 99%
“…Comparatively, during the strongest contraction, the preterm group seems to behave similarly to parasympathetic blocked subjects in preclinical studies. For example, parasympathetic blocked sheep fetuses (through vagotomy or atropine administration) present higher FHR during and after umbilical cord occlusions in comparison with a control group (non-blocked fetuses) (35,38).…”
Section: Discussionmentioning
confidence: 99%
“…Individual periods of acute hypoxaemia are sensed by the chemoreceptors of the aortic arch and carotid body, activating the peripheral chemoreflex and increasing parasympathetic and sympathetic neural outflow. The parasympathetic arm triggers a rapid fall in FHR (Lear et al 2021;Recher et al 2021), observed clinically as intrapartum decelerations (Lear et al 2016b). The sympathetic arm triggers profound peripheral vasoconstriction across multiple vascular beds (Giussani et al 1993), which increases arterial blood pressure to All studies were undertaken at approximately 0.85 of gestation, broadly equivalent to the neural maturation of the full-term human fetus.…”
Section: The Physiology Of Labour and Fetal Adaptationmentioning
confidence: 99%